Predictive Factors for Improvement of Atrophic Gastritis and Intestinal Metaplasia: A Long-term Prospective Clinical Study - Young-Jae Hwang; Nayoung Kim; Chang Yong Yun; Min Gu Kwon; Sung Min Baek; Yeong Jae Kwon; Hye Seung Lee; Jae Bong Lee; Yoon Jin Choi; Hyuk Yoon; Cheol Min Shin; Young Soo Park; et al. (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: To investigate the predictive factors for improvement of atrophic gastritis (AG) and intestinal metaplasia (IM). Materials and Methods : A total of 778 subjects were prospectively enrolled and followed up for 10 years. Histological analysis of AG and IM was performed by using the updated Sydney system. To find the predictive factors for reversibility of AG and IM, 24 factors including genetic polymorphisms and bacterial and environmental factors were analyzed. Results : In all subjects, the predictive factor by multivariate analysis for improvement of both antral and corpus AG was successful eradication. The predictive factors for improvement of antral IM were age and successful eradication. The predictive factor for improvement of corpus IM was successful eradication. In patients with Helicobacter pylori infection, age and cagA were predictive factors for improvement of AG and IM. In patients with H. pylori eradication, monthly income and cagA were predictive factors for improvement of AG and IM. Conclusions : H. pylori eradication is an important predictive factor of regression of AG and IM and would be beneficial for the prevention of intestinal-type gastric cancer. Young age, high income, and cagA are additional predictive factors for improving AG and IM status. Thus, various factors affect the improvement of AG and IM.